NITROGEN-FIXING AEROBIC BACTERIA AND THEIR NITROGENASE ACTIVITY IN NORTH MUJ. IBAI COASTAL - Pandey, P. K.; Sreelu, N. S. (Journal of Indian Fisheries Association, 2006)
The effect of the physicochemical parameters of water and soH on the distribution of nitrogen-fixing bacteria and their nitrogen-fixing capacity was studied. Four species of nitrogen-fixing bacteria, e. g., Azotobacter chroococcunz, A. vinelandii, A. beijerinckii and A. armeniacu. ., · were recorded from water and soil samples of Mumbai coast. A higher number of bacterial populations were observed in sediment than in water samples. A positive correlation was observed between the dissolved organic matter and nitrogenfixing bacterial populations of water as well as between available phosphorus and the nitrogen-fixing bacteria of sediment. The nitrogen-fixing capacity of A. chroococcum was found to be 1.076 nmol C2H./l/d and that of A. vinelandii was 0.965 nmol C2H/l/d. Station 1 showed higher level of nitrogenase activity in comparison to other four stations. Keywords: Nitrogen-fixing bacteria,AzotobacteJ nitrogenase activity